Frequency of NAFLD among Patients of Coronary Artery Disease - Zaryab Khan, Hoor Ul Ain, Sheeba Faryal, Habiba Inayat, Faizan Ahmed, Wasfa Aijaz (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to assess the prevalence of NAFLD in coronary artery disease patients. Study Design: Prospective study Place and Duration: Department of General Medicine, Khyber Teaching Hospital, MTI Peshawar in the duration from June, 2022 to November, 2022. Methods: Total 125 patients of both genders with age 25-75 years were presented. Patients were included if they had a verified diagnosis of CAD and stenosis in either of the main coronary arteries or one of the branches. Hepatic steatosis was diagnosed with ultrasound of the liver in all individuals. Likewise, steatosis severity was ranked from 0 (no steatosis present) to 3 (moderate steatosis present) (severe steatosis). At last, the patients’ NAFLD prevalence was calculated. The data was analyzed using SPSS 23.0. Results: In all, 73 (58.4%) patients were males and 52 (41.6%) cases were females. Mean age of the patients was 44.6±18.37 years and had mean BMI 26.9±11.65 kg/m2. Most common comorbidity was hypertension, followed by diabetes mellitus, obesity and hyperlipidemia. There were 60 (48%) smokers among all cases. Frequency of NAFLD was found in 62 (49.6%) cases. Among 62 cases of NAFLD, 40 cases were had normal NAFLD (grade 1) and 22 cases were had mild NAFLD (grade 2). Majority of the NAFLD patients were had hyperlipidemia, obesity and hypertension. Conclusion: We found that obese, HTN, and hyperlipidemic NAFLD individuals were more common. The prevalence and severity of NAFLD were also independently linked with CAD. Normal vascular and NOB patients had mild NAFLD, while extensive CAD patients with multi-vessel disease had severe NAFLD. Keywords: CAD, NAFLD, Obesity, Hyperlipidemia, HTN